Diseño de una guía digital a partir de las interacciones entre la fauna silvestre y los habitantes del caserío el placer, parroquia Río Verde, cantón Baños, Provincia de Tungurahua - Ipiales Montenegro, Elizabeth Marisol (2022)
This research study was conducted within the zone of influence of the Llanganates Sangay ecological corridor, specifically in ‘El Placer’ country house, Rio Verde Parish, Baños Canton, Tungurahua Province. As it is a site full of biodiversity, the existence of both positive and negative interactions is common, which has led to a decrease in the tolerance of the inhabitants to wildlife, since some of these species have been poisoned in different circumstances and times. The lack of knowledge of the species at the ecological, tourist, and socio-cultural levels is an important factor in environmental education. Therefore, it was proposed to design a digital guide on interactions, for which descriptive research with a qualitative approach was carried out, identifying the study zones and the interactions through literature review, interviews, and field trips. It resulted in 2 registration zones: zone 1 - called low montane evergreen forest because it is located at an altitude ranging from 1454 to 1455 m.a.s.l. This zone has 3 points of direct and indirect interactions of wildlife species such as cougar, spotted ocelot, and long-tailed weasel, while zone 2, or bear route, covers an altitude of 1474 to 2289 m.a.s.l. with the interaction of the spectacled bear and capuchin monkey. For the development of the species register, a camera trap, camera, GPS, and registration forms adapted to the study area were used to verify the presence of the Andean bear, also known as the spectacled bear, through indirect records such as footprints, cow remains and the tree where it rested and fed. This species is in conservation status according to the IUCN as vulnerable, while the red book of mammals of Ecuador is in a state of danger. Finally, the information was systematized in an interactive digital guide that allows the dissemination of knowledge through videos, images, and maps. The aim of this research study is to promote their names and importance from an ecological, touristic, and socio-cultural point of view, and to encourage the conservation and appropriate use of them, since most of them are in a vulnerable and endangered level of conservation, developing scientific tourism based on them in the future.